Pain and Functional Outcome with Single dose 25% Dextrose Intra-Articular Injection in Patients with Primary Osteoarthritis of the Knee (Journal of Dhaka Medical College, 2021)
Introduction: Osteoarthritis (OA) is the most prevalent chronic joint disorder worldwide and is associated with significant pain and disability. The introduction of 25% Dextrose injection has been viewed as an advance in the management of OA knee.Methods: A prospective, randomized clinical trial was conducted with 84 cases in the Physical Medicine and Rehabilitation (PMR) department of BSMMU. Group A, 42 patients received single dose 25% Dextrose injection intra articular 8ml, exercise and ADL; Group B, 42 patients received exercise and ADL. Outcomes were measured by OA specific translated and validated Bengali instrument- Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire and visual analogue scale (VAS 0-10). They were followed up for 6 months.Result: At the initial stage and in week 4, there was no statistical difference between two groups regarding VAS score (as p value was >0.05). But in week 12 and 24, there was highly significant statistical difference regarding VAS score between two groups as the p value was